PROJECTION OF RICE PRODUCTION IN MUSI RAWAS REGENCY - Octalia, Vera; Primalasari, Ira (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
This research aims to determine rice production in Musi Rawas Regency from 2010- 2023 and analyze rice production projections in Musi Rawas Regency from 2024-2030. This research is quantitative descriptive research. The data source used in this research is secondary data. Secondary data is rice production time series data. The processed results are presented in the form of tables and graphs. The results of this research show that the forecasting results for paddy production and rice production in Musi Rawas Regency for 2024-2030 experienced a decrease in paddy and rice production. This decline occurred because the final forecast value in the model was negative. The decrease in rice production in 2024-2025 is based on the forecast of 352 tons https://www.fortyouncewines.com/ and rice production of 224 tons. Each year, rice production decreases by 1 to 2 tons and rice production decreases by 0.3 to 1.2 tons per year.